RESTORATIONS WITH CERAMIC LAMINATES AND THE INDICATIONS AND CONTRAINDICATIONS OF THIS TREATMENT: LITERATURE REVIEW - Filho, Rubens Monari de Queiroz; Cesnik, Ana Beatriz; Franzin , Cláudio Alberto; Franzin, Lucimara Cheles da Silva; Torchi, Sandra de Oliveira; de Souza , Ilma Carla (Seven Editora, 2024)
The search for restorations with ceramic laminates has been one of the main topics in dentistry today, since these restorations can reestablish aesthetics while having an extensive longevity. Therefore, ceramic laminates can positively influence the self-esteem of patients, promoting satisfaction in relation to their smile. The aim of this study was to review the literature, showing the indications and contraindications of restorations with ceramic laminates and the reasons that induce success or failure in this type of treatment, as well as its limitations. In view of the above, it is important to know the parameters to be evaluated before planning a treatment with ceramic laminates, in order to achieve clinical success. DOI:https://doi.org/10.56238/sevened2024.031-006